IGBO POST-CONTACT PROVERBS OF THE INYI COMMUNITY - Unaegbu, Jephthah Elochukwu (Proverbium - Yearbook, 2020)
This article is on post-contact proverbs in Inyi community of southeastern Nigeria. Before now, there is no ethnography on post-con-tact Inyi proverbs. To acquire data, the researcher used the quantitative research method. Interview schedule and participant observation are the instruments of data collection. Post-contact proverbs in Inyi were obtained from Umunna meetings and traditional marriage ceremonies and also from respondents who are Okenyes or Inyi elders versed in Inyi culture. The meanings of these proverbs and the occasions in which they are used were also obtained. Forty-four post-contact proverbs were collected during the fieldwork. The eleven (11) contact proverbs which were obtained during participant observation were utilized by Inyi indigenes who were younger than the Okenyes. The remaining thirty-three post-contact proverbs came from the Okenyes. The need for a wider study of Igbo post-contact proverbs is advanced.